Simulation and Experimental Study on Properties of Ag/SnO2 Contact Materials Doped with Different Ratios of Ce - Jingqin Wang; Ying Zhang; Huiling Kang (Advances in Materials Science and Engineering)
SnO2 in the Ag/SnO2 contact material is a kind of high hardness and almost insulated wide bandgap semiconductor material. In the process of use, the contact resistance is larger and the temperature rise is higher, which reduces the reliability of contacts and shortens the electrical life. In order to improve the properties of Ag/SnO2 contact materials, based on the first principle of density functional theory, this paper presents a method of doping SnO2 with the calculation of different proportions of rare earth Ce electrical and mechanical properties. The results of energy band, density of state, and elastic constant show that when the doping ratio of Ce is 0.125, the electron mobility is the highest, the conductivity is the best; the hardness decreases, and the universal elastic anisotropy index is the smallest. Finally, in the experiment, SnO2 powders with different doping ratios are prepared by the sol-gel method, and Ag/SnO2 contacts with different doping proportions are prepared by powder metallurgy. Arc energy, contact resistance, and hardness are measured; scanning electron microscopy was used to observe and analyze the surface morphology. The final simulation and experimental results are well matched.